Characterization of Escherichia coli Strains Isolated from Patients with Diarrhea in São Paulo, Brazil: Identification of Intermediate Virulence Factor Profiles by Multiplex PCR - Liebchen, Ariane (American Society for Microbiology, 2011)
Intestinal pathogenic Escherichia coli is a major causative agent of severe diarrhea. In this study the prevalences of different pathotypes among 702 E. coli isolates from Brazilian patients with diarrhea were determined by multiplex PCR. Interestingly, most strains were enteroaggregative E. coli (EAEC) strains, followed by atypical EPEC (ATEC) strains. Classical enteropathogenic E. coli (EPEC) strains were not detected.